2000
DOI: 10.1063/1.126057
|View full text |Cite
|
Sign up to set email alerts
|

The use of a surfactant (Sb) to induce triple period ordering in GaInP

Abstract: A surfactant is used to induce an ordered structure in an epitaxial layer. The addition of small amounts of triethylantimony during the organometallic vapor phase epitaxy growth of GaInP on (001) GaAs substrates is shown to remove CuPt ordering with a resultant increase in band gap energy. Increasing the concentration of Sb in the vapor beyond a critical Sb to P ratio [Sb/P(v)] of 4×10−4 gives a reversal of this behavior. The band gap energy is observed to decrease by 50 meV at a concentration of Sb/P(v)=1.6×1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 14 publications
2
27
0
Order By: Relevance
“…A lot of work has been conducted on the adsorption and deposition of Bi on Si (0 0 1) [4,5] on MBE growth. In OMVPE growth, surfactants can induce strong bulk effects such as the suppression of atomic ordering [3,6] and improvement in surface morphology [2], of many III-V materials without incorporation in the bulk. Recent works have shown that reflectance difference spectroscopy (RDS) is extremely sensitive to surface adsorbates such as Sb on GaAs and InP [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…A lot of work has been conducted on the adsorption and deposition of Bi on Si (0 0 1) [4,5] on MBE growth. In OMVPE growth, surfactants can induce strong bulk effects such as the suppression of atomic ordering [3,6] and improvement in surface morphology [2], of many III-V materials without incorporation in the bulk. Recent works have shown that reflectance difference spectroscopy (RDS) is extremely sensitive to surface adsorbates such as Sb on GaAs and InP [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of the Bi/ InSb͑100͒c͑2 ϫ 6͒ surface properties is essential not only for understanding the detailed formation mechanisms of the technologically important c͑2 ϫ 6͒ reconstructions but also for understanding the Bi surfactant-mediated growth of III-V's. 13,14 The Bi/ InSb͑100͒c͑2 ϫ 6͒ substrate also represents a starting surface to study the growth phenomena of the epitaxial Bi and MnBi films, [15][16][17] which both are almost lattice matched to the InSb substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Later, it was found that surfactants can reduce interface roughness [8]. In 2000, the introduction of surfactants was found to effectively change surface reconstructions, the strain distributions, and the alloy ordering [9]. Also, the surfactants can change the electronic structure of the thin film and tune the doping [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 97%
“…Recent theoretical and experiment works suggest that indeed, external strains can affect the doping properties of bulk and thin film materials [15][16][17][18][19]. Sometimes, there is also interplay between strain and surfactant at semiconductor thin film surfaces [9].…”
Section: Introductionmentioning
confidence: 98%